Intracellular pathogens convert macrophages from death traps into hospitable homes. (2nd February 2016) - Barbier, Julien; Cintrat, Jean‐Christophe; Gillet, Daniel
Abstract : Intracellular pathogens – bacteria, parasites and fungi – frequently infect macrophages in addition to other cells. They turn these deadly cells into harmless hosts to multiply and paralyze immunity. Understanding the complex mechanisms underlying this phenomenon may have a strong impact to identify new targets belonging to the pathogens but also to the host, thereby allowing the design of new therapeutic strategies.